2021
DOI: 10.1371/journal.pone.0258811
|View full text |Cite
|
Sign up to set email alerts
|

Association between prehospital field to emergency department delta shock index and in-hospital mortality in patients with torso and extremity trauma: A multinational, observational study

Abstract: Hemorrhage, a main cause of mortality in patients with trauma, affects vital signs such as blood pressure and heart rate. Shock index (SI), calculated as heart rate divided by systolic blood pressure, is widely used to estimate the shock status of patients with hemorrhage. The difference in SI between the emergency department and prehospital field can indirectly reflect urgency after trauma. We aimed to determine the association between delta SI (DSI) and in-hospital mortality in patients with torso or extremi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Schellenberg et al ( 29) included 1,294 patients with trauma and showed that the ED delta SI was strongly predictive of mortality, need for blood product transfusion, and ICU length of stay. Kim et al (30) reported similar results regarding the association between delta SI and inhospital mortality in patients with torso or extremity traumas. However, the prehospital transport time in Taiwan is generally less than 20 min.…”
Section: Discussionmentioning
confidence: 61%
“…Schellenberg et al ( 29) included 1,294 patients with trauma and showed that the ED delta SI was strongly predictive of mortality, need for blood product transfusion, and ICU length of stay. Kim et al (30) reported similar results regarding the association between delta SI and inhospital mortality in patients with torso or extremity traumas. However, the prehospital transport time in Taiwan is generally less than 20 min.…”
Section: Discussionmentioning
confidence: 61%
“…Two studies involved the geriatric population [ 33 , 35 ], while Montoya et al [ 36 ] considered only patients younger than 50 years old. Seven studies excluded patients with traumatic brain injuries (TBI) [ 17 , 21 , 32 , 33 , 35 , 37 , 41 ]. Some variability was observed regarding the definition of MT and mortality.…”
Section: Resultsmentioning
confidence: 99%
“…Some variability was observed regarding the definition of MT and mortality. Almost all studies defined MT as 10 red blood cells (RBC units within 24 h [ 19 , 21 , 22 , 28 , 38 , 40 , 42 , 44 , 47 , 51 , 52 ] and mortality as in-hospital mortality [ 18 , 22 , 25 29 , 31 , 33 35 , 38 , 41 ]. Different definitions are a further source of potential heterogeneity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a single data point of vital signs and GCS in a progressive injury may not always reflect the clinical condition. Many studies have been suggested using a series of follow-up scoring systems to improve prediction accuracy, such as delta SI ( 31 , 32 ). Series rSIG measurement not only reflects the disease progression but also decreases the impairment of measure time variation.…”
Section: Discussionmentioning
confidence: 99%